AB0229 Does Serum Level of IL-17 Affect Disease Activity and Functional Disability in Rheumatoid Arthritis Patients? Relation between Serum IL-17 Level, DAS-28 and HAQ-DI. (15th July 2016) - Aboeladl, N.A.; Koryem, H.K.; Rezk, M.A.; Hassan, M.M.; Eltawab, S.S.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, progressive, systemic inflammatory disease. Interleukin-17 (IL-17) is a cytokine that is expressed in inflammatory and autoimmune diseases and expected to play an important role in the pathogenesis of RA. Many years, the measurement of disease activity in RA has been held by Disease Activity Score-28 (DAS-28). Regarding the correlation between serum level of IL-17 and disease activity, some authors found a good significant correlation between these parameters, while others stated that DAS-28 values for expressing disease activity in RA patients may be flawed by coexisting fibromyalgia lead to higher total scores. Health Assessment Questionnaire –Disability Index (HAQ-DI) has been usually used for disability assessment in RA patients. It is one of the most widely used comprehensive, validated and patient-oriented outcome assessment instruments. Objectives: To study the relation between serum IL-17 level, DAS-28 CRP and HAQ-DI in RA patients. Methods: The study included 25 RA patients and 20 healthy controls. Serum IL-17 was measured by ELISA, disease activity by DAS-28 CRP and functional disability by HAQ-DI. Results: Serum IL-17 level among RA patients was significantly higher than healthy control ( p <0.001). Serum IL-17 levels showed insignificant correlation with DAS-28 CRP and HAQ-DI of RA patients. Conclusions: IL-17 doesnot correlate with disease activity and functional disability in RA patients. References: McInnes I, Schett G. The pathogenesis of rheumatoid arthritis. N Engl J Med 2011; 365:2205–19. Rosu A, Margaritescu C, Stepan A, Musetescu A, Ene M. IL-17 patterns in synovium, serum and synovial fluid from treatment-naive, early rheumatoid arthritis patients. Rom J Morphol Embryol 2012; 53(1):73–80. Van Riel PL, Scott DL. EULAR handbook of clinical assessment in rheumatoid arthritis. 2000; 2:13–34. Singh H, Kumar H, Handa R, Talapatra P, Ray S, Gupta V. Use of Clinical Disease Activity Index Score for Assessment of Disease Activity in Rheumatoid Arthritis Patients: An Indian Experience. Arthritis 2011; 2011:1–5. Rosu A, Margaritescu C, Stepan A, Musetescu A, Ene M. IL-17 patterns in synovium, serum and synovial fluid from treatment-naive, early rheumatoid arthritis patients. Rom J Morphol Embryol 2012; 53(1):73–80. Yue C, You X, Zhao L, Wang H, Tang F, Zhang F, et al. The effects of adalimumab and methotrexate treatment on peripheral Th17 cells and IL-17/IL-6 secretion in rheumatoid arthritis patients. Rheumatol Int 2010; 30(12):1553–7. Leeb BF, Andel I, Sautner J, Nothnagl T, Rintelen B. The DAS28 in rheumatoid arthritis and fibromyalgia patients. Rheumatology 2004; 43(12):1504–7. Genovese MC, Van den Bosch F, Roberson SA, Bojin S, Biagini IM, Ryan P, et al. LY2439821, a humanized anti-interleukin-17 monoclonal antibody, in the treatment of patients with rheumatoid arthritis. Arthritis Rheum 2010; 62(4):929–39. Acknowledgement: Deep thanks to my professors, parents and my husband. Disclosure of Interest: None declared